2017
DOI: 10.1111/jre.12470
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cross‐linked vs non‐cross‐linked collagen membranes on bone: A systematic review

Abstract: The aim of this study was to conduct a systematic review to compare the clinical outcomes of two different resorbable collagen membranes in terms of regenerated bone volume, postoperative complications and membrane degradation during bone regeneration procedures. Randomized controlled trials (RCT) or controlled trials (CT) that compared both techniques were reviewed on four electronic databases up to December 2015, a manual search was performed on the bibliography of the collected articles and the authors were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 57 publications
(139 reference statements)
0
31
0
2
Order By: Relevance
“…It has been suggested that a 1-month barrier function time for each millimeter of bone regeneration is needed [43]. Garcia et al [44] in their study state that GBR procedures through resorbable CM achieve volumetric bone gains with no statistical significance between the cross-linked and the non-cross-linked membranes. Moses et al [45] also reported no substantial difference in preserving hard and soft tissue volume between cross-linked and non-cross-linked membranes.…”
Section: Native Vs Cross-linked Collagenmentioning
confidence: 99%
“…It has been suggested that a 1-month barrier function time for each millimeter of bone regeneration is needed [43]. Garcia et al [44] in their study state that GBR procedures through resorbable CM achieve volumetric bone gains with no statistical significance between the cross-linked and the non-cross-linked membranes. Moses et al [45] also reported no substantial difference in preserving hard and soft tissue volume between cross-linked and non-cross-linked membranes.…”
Section: Native Vs Cross-linked Collagenmentioning
confidence: 99%
“…Cha et al () demonstrated the high biocompatibility and absence of a foreign body reaction when using a cross‐linked membrane. However, Jiménez Garcia, Berghezan, Caramês, Dard, and Marques () found no difference between cross‐linked and non‐cross‐linked membranes in terms of the regenerated bone volume.…”
Section: Introductionmentioning
confidence: 97%
“…Jiménez Garcia et al performed a systematic review of the effects of cross‐linked versus noncross‐linked collagen membranes on guided bone regeneration (GBR) techniques (Jiménez Garcia, Berghezan, Caramês, Dard, & Marques, ). Both types of collagen membranes achieved good volumetric bone gains without statistical significance between the cross‐linked and the noncross‐linked collagen membranes; however, the comparison of postoperative complications showed higher rates of postoperative complications, including membrane exposure, for cross‐linked membranes (Jiménez Garcia et al, ). This might be explained by interference with the inflammatory response and soft tissue healing, resulting in tissue integration and possibly bone regeneration (Rothamel et al, ).…”
Section: Introductionmentioning
confidence: 99%